Multiple fashion: inclusive experience in context of Down syndrome (Revista de Ensino em Artes, Moda e Design, 2023)
This article provides experiences of social inclusion from the extension program entitled “Moda Múltipla” (“Multiple Fashion”). The project was carried out through a multidisciplinary approach that encompassed undergraduate courses in fashion design, graphic design, law and psychology. Founded in 2022, it was completed in partnership with Associação Vitória Down. Using social transformation as a focus “Moda Múltipla” sought to create a partnership between teaching, research, and extension. Through inclusive fashion, graffiti, and design practices that value and bring people closer to a humane world, it impacted students and the external community. Considering the vulnerability of people with Down Syndrome, both as consumers and as protagonists of fashion, an attempt was made to understand the needs and difficulties of the public, especially in relation to clothing items, as well as to strengthen their representativeness in the field, respecting the narratives of each participant's life stories. The project culminated in the exchange of several actions, including the customization of pieces based on artisanal printing and illustration techniques. In addition, there was fashion editorials, fashion show and photographic exhibition held in a shopping mall, and graffiti on the wall of the institution Vitória Down. We can use the results to rethink the fashion system, minority representation, and create pedagogical strategies in favor of diversity.
Keywords: Down syndrome; fashion; social inclusion